Kualitas Aset dan Likuiditas dalam Mempengaruhi Kinerja Keuangan PT Bank Mega Syariah Tbk - Tiara fitri rizkiyah (Jurnal Wacana Ekonomi, 2018)
This study aims to determine the description of asset quality or Non-Performing Financing (NPF), liquidity or Finanacing to Deposit Ratio (FDR), profitability or Return ON Equity (ROE), as well as the effect of asset quality and liquidity on profitability at Bank Syariah Mega Indonesia. The method used in this research is descriptive and verification using secondary data with a sample of data for the period 2009-2017 that has been published by Bank Syariah Mega Indonesia. The results of this study are The NPF, FDR, and ROE values of Bank Syariah Mega Indonesia experience fluctuating movements from year to year. Based on the results of simultaneous statistical tests, it can be concluded that asset quality (NPF) and liquidity (FDR) have a relationship with profitability (ROE). Asset quality has an influence with a negative coefficient while asset quality has an influence with a positive coefficient on the profitability of Bank Syariah Mega Indonesia. Asset quality (NPF) and liquidity (FDR) simultaneously and jointly affect profitability (ROE).